In-hospital Outcomes and Long-term Survival after Off-Pump and On-Pump Redo Coronary Artery Bypass Grafting: A Propensity Matched Analysis - Asif, Muhammad Saad; Wajid, Muhammad Talha; Marczin, Nandor; Bhudia, Sunil K.; Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2026)
Background: Redo coronary artery bypass grafting (redo-CABG) carries substantial perioperative risk, and comparative evidence between on-pump and off-pump approaches remains limited. This study evaluates short-term outcomes and long-term survival in patients undergoing redo-CABG with (on-pump) or without cardiopulmonary bypass (off-pump). Methods: We retrospectively analyzed 191 patients undergoing redo-CABG (off-pump: n=143; on-pump: n=48) from 2006–2019. Primary endpoints included 30-day mortality, re-exploration, re-intubation/tracheostomy, and hemofiltration; secondary endpoint was long-term survival. Propensity score matching (1:1, caliper 0.20) yielded 40 well-balanced pairs. Kaplan–Meier analysis and Cox regression assessed survival and predictors of mortality. Results: In the unmatched cohort, 30-day mortality was similar (8.4% off-pump vs 6.3% on-pump, p=0.76). Off-pump patients required fewer transfusions (22.4% vs 43.8%, p=0.01), received fewer grafts (median 2 vs 3, p<0.001), and had lower index of completeness of revascularization scores (0.87±0.39 vs 1.03±0.25, p=0.001). In matched cohorts, 30-day and in-hospital mortality did not differ (12.5% vs 2.5%, p=0.20), but all on-pump patients required transfusion versus none off-pump (p<0.001). Long-term survival was comparable (10-year: 63.5% vs 73.7% unmatched; 68.7% vs 74.3% matched; log-rank p=0.20 and p=0.52, respectively). Independent predictors of long-term mortality included peripheral vascular disease (HR 2.44, p=0.006), operative urgency (HR 2.20, p=0.005), and age (HR 1.04, p=0.021). Conclusions: Off-pump redo-CABG offers similar short- and long-term outcomes to on-pump surgery, with reduced transfusion needs. Both techniques remain viable, with selection guided by patient factors, anatomy, and surgical expertise.